Towards robust Pseudomonas cell factories to harbour novel biosynthetic pathways - Bitzenhofer, Nora Lisa; Kruse, Luzie; Thies, Stephan; Wynands, Benedikt; Lechtenberg, Thorsten; Rönitz, Jakob; Kozaeva, Ekaterina; Wirth, Nicolas Thilo; Eberlein, Christian; Jaeger, Karl-Erich; Nikel, Pablo Iván; Heipieper, Hermann J.; et al. (Essays in Biochemistry, 2021)
Abstract Biotechnological production in bacteria enables access to numerous valuable chemical compounds. Nowadays, advanced molecular genetic toolsets, enzyme engineering as well as the combinatorial use of biocatalysts, pathways, and circuits even bring new-to-nature compounds within reach. However, the associated substrates and biosynthetic products often cause severe chemical stress to the bacterial hosts. Species of the Pseudomonas clade thus represent especially valuable chassis as they are endowed with multiple stress response mechanisms, which allow them to cope with a variety of harmful chemicals. A built-in cell envelope stress response enables fast adaptations that sustain membrane integrity under adverse conditions. Further, effective export machineries can prevent intracellular accumulation of diverse harmful compounds. Finally, toxic chemicals such as reactive aldehydes can be eliminated by oxidation and stress-induced damage can be recovered. Exploiting and engineering these features will be essential to support an effective production of natural compounds and new chemicals. In this article, we therefore discuss major resistance strategies of Pseudomonads along with approaches pursued for their targeted exploitation and engineering in a biotechnological context. We further highlight strategies for the identification of yet unknown tolerance-associated genes and their utilisation for engineering next-generation chassis and finally discuss effective measures for pathway fine-tuning to establish stable cell factories for the effective production of natural compounds and novel biochemicals.